Fiqh Munakahat Education at Islamic Boarding School: A Bridge between Classical Texts, Attitudes, and Contemporary Needs - Rahmi, Muarifah (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Islamic intellectual literature is used to teach fiqh munakahat at As'adiyah Sengkang Islamic Boarding School. This program finds it difficult to prepare students for the challenges posed by millennial families, changing gender roles, marriage, and technology. This article analyzes how As'adiyah Sengkang Islamic Boarding School meets students' practical requirements through dogmatic textual understanding and mature (affective) attitudes. This study evaluates the As'adiyah Sengkang Islamic Boarding School's Fiqh Munakahat curriculum and ancient literature instruction. This qualitative study employs one case study (As'adiyah Sengkang Islamic Boarding School). Data was collected through classroom observations (deliberation and discussion), in-depth interviews with pesantren leaders (kyai), Fiqh teachers (ustaz/ustazah), and final-year students (santri), and curriculum document analysis. The study found that As'adiyah Sengkang Islamic Boarding School mediates. The pesantren successfully maintains traditional texts as the basis of law, including the Fathul Qarib and Taqrib volumes. Non-curricular initiatives, including premarital seminars, family psychology topic discussions, and home digital literacy halaqah (religious gatherings), include modern elements. This instructional change emphasizes legal validity and nullity as well as effective and practical capacity building (sustainability and harmony). This article improves Islamic boarding school curriculum and education research. These findings can help other Islamic boarding schools develop a holistic, relevant, and current Munakahat Fiqh curriculum that upholds Islamic science.